2019
DOI: 10.4103/ijpc.ijpc_51_19
|View full text |Cite
|
Sign up to set email alerts
|

Current asbestos exposure and future need for palliative care in India

Abstract: Asbestos-related diseases (ARDs) are incurable but entirely preventable. Due to India's continuing use of asbestos, ARD patients will increase to a high number in the next three to four decades. This will increase the burden on palliative care system which is in nascent stage presently. Palliative care is the mainstay of the management of ARDs. Unfortunately, the burden on palliative care is likely to increase due to multiple factors contributed by India's demographic and economic changes. In the near future, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Access to palliative care is crucial for patients with MPM, particularly in developing nations where access to specialist care or anti-neoplastic therapies can also be limited. 11 Palliative care describes the active approach towards patients with life-limiting illnesses to reduce suffering through accurate assessment and treatment of physical symptoms, as well as psychosocial and spiritual aspects. Palliative care has a role at any time after diagnosis with the aim of enhancing quality of life, comfort, and preserving dignity.…”
Section: The Importance Of Palliative Care In Mpmmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to palliative care is crucial for patients with MPM, particularly in developing nations where access to specialist care or anti-neoplastic therapies can also be limited. 11 Palliative care describes the active approach towards patients with life-limiting illnesses to reduce suffering through accurate assessment and treatment of physical symptoms, as well as psychosocial and spiritual aspects. Palliative care has a role at any time after diagnosis with the aim of enhancing quality of life, comfort, and preserving dignity.…”
Section: The Importance Of Palliative Care In Mpmmentioning
confidence: 99%
“…MPM is rarely diagnosed in these countries, which is at odds with the known industrial history and activity. 7,[11][12][13] For example, there were no deaths related to mesothelioma reported to the World Health Organization between 1994 and 2008 in China, India, and Indonesia. 14,15 There is likely a significant lack of recognition, related to poor awareness and access to diagnosis, incomplete reports to local cancer registries, and a lack of local registries for cancer or occupational disease, in addition to insufficient latency periods since the introduction of industrial use of asbestos.…”
Section: Introductionmentioning
confidence: 99%
“…In India, a country consuming more than 300,000 metric tons of asbestos each year, governmental representatives claim that they cannot deny the poor a cheap asbestos roof above their head and argue that this is more important than curtailing the environmental asbestos disaster that is currently unfolding. Poor people will be the first bear the brunt of the tragic consequences: 1.25 million asbestos-related cancer patients are expected in India, which already has a major lack of palliative care facilities [89]. Every year on the beaches of India, Pakistan and Bangladesh, hundreds of large ocean ships are dismantled with no or lax environmental regulations.…”
Section: Susceptibility Factors Smoking and Asbestos Long-term Consequences Of A Contaminated Environment And The Failure To Register Allmentioning
confidence: 99%
“…Nonetheless, asbestos was still consumed in 39 countries worldwide in 2017 ( Figure 9) and 0 1,000,000 2,000,000 3,000,000 4,000,000 5,000,000 1900 1910 1920 1930 1940 1950 1960 1970 1980 1990 2000 2010 2017 Mass production (t) production continued in four, with Russia producing nearly two thirds of the 1.1 Mt consumed worldwide that year ( Figure 10). use is apparent in India (Figure 11), where there are no restrictions on its production and consumption (Jadhav and Gawde, 2019). Specific data are not available, but it has been reported that in India almost all asbestos is used in cement bonded sheet material (Burki, 2010), and the International Chrysotile Association (nd) reports a similar picture elsewhere.…”
Section: Asbestosmentioning
confidence: 99%